The Development of Masters Studies in Education Management - Želvys, Rimantas (Acta Paedagogica Vilnensia, 2003)
The article deals with the problem of ensuring the quality of masters studies in education management and foreseeing tendencies of development of masters studies in the future. The author points out the need to make a clear distinction between strategic, tactical and operative functions of school principles. These levels should he accordingly represented by courses on education policy, education management and educational administration. The article argues that the contents of master’s studies is closely linked with the level of centralization of the country’s educational system. In a decentralized system the main focus of the master’s program should be directed towards policy issues while in a highly centralized system courses on educational administration prevail. The article also analyses selected MA programs on education management in Sweden. UK and Lithuania. The results of the analysis shows the tendency of Lithuanian masters programs to move gradually from the Scandinavian towards the British model, which implies that more subjects on general management are being introduced at the expense of narrowly specialized courses on education and educational administration.